The role of emotion dysregulation in adolescents' problematic smartphone use: A study on adolescent/parents triads. (February 2021) - Giordano, Cecilia; Lo Coco, Gianluca; Salerno, Laura; Di Blasi, Maria
Abstract: The pervasive use of mobile phones among adolescents has led researchers to evaluate the role of parental characteristics in connection with their children's problematic smartphone use (PSU). The present study involved mother/father/adolescent triads and aimed to test a model examining the role of both parents' and adolescents' emotion dysregulation (ED) in predicting children's PSU. Two hundred and fifty-two adolescent (57.5% females; M age = 13.54, SD = 0.73)/mother (M age = 43.92, SD = 4.46)/father (M age = 47.60, SD = 5.10) triads provided measures of PSU and ED. Results from path model showed that, after controlling for adolescents' age and gender as well as for parents' age and low well-being, both adolescents' and parents' ED was related to their own PSU (intra-individual level). Contrary to hypotheses, no direct relation was found between either parents' and adolescent's PSU (inter-individual level). However, adolescents' ED mediated the relationship between mothers' emotion dysregulation and adolescents' PSU. The results demonstrate the importance of considering parents' level of ED when examining the link between PSU and ED among adolescents. Highlights: Problematic smartphone use (PSU) was examined in adolescent/parent triads. Two hundred and eighty-two adolescent/mother/father triads were included. Both adolescents' and parents' PSU were linked to their own emotion dysregulation. No direct relation was found between either parents' and adolescent's PSU. Mothers' emotion dysregulation had an indirect effect on adolescents' PSU.